1986
DOI: 10.1128/aac.29.5.803
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of borate-buffered solutions

Abstract: A minimal salts medium adjusted to physiological pH and osmolality was buffered with either 0.3% phosphate or 1.2% borate and evaluated for antimicrobial activity. The borate-buffered medium, either with or without a carbon source, exhibited significant antimicrobial activity against 15 Pseudomonas strains, 12 strains of enteric bacteria, and 7 strains of staphylococci. The borate-buffered system appears suitable for use as a generic vehicle for ophthalmic pharmaceutical agents.In 1958, Kingma summarized the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…Solutions containing borate ions in combination with chlorhexidine effectively inhibited unadapted S. marcescens with linear killing kinetics, whereas cells adapted to phosphate-buffered chlorhexidine showed biphasic killing curves in borate-buffered chlorhexidine. Antimicrobial activity of borate solutions for ophthalmic products has been noted by Houlsby et al (14). Ogunbiyi et al (21) reported that borate ions enhanced the activity of polyhexamethylene biguanides, and Wilson et al (27) noted relatively greater inhibitory activity for several contact lens solutions containing borate versus phosphate buffers.…”
Section: Discussionmentioning
confidence: 88%
“…Solutions containing borate ions in combination with chlorhexidine effectively inhibited unadapted S. marcescens with linear killing kinetics, whereas cells adapted to phosphate-buffered chlorhexidine showed biphasic killing curves in borate-buffered chlorhexidine. Antimicrobial activity of borate solutions for ophthalmic products has been noted by Houlsby et al (14). Ogunbiyi et al (21) reported that borate ions enhanced the activity of polyhexamethylene biguanides, and Wilson et al (27) noted relatively greater inhibitory activity for several contact lens solutions containing borate versus phosphate buffers.…”
Section: Discussionmentioning
confidence: 88%
“…It was also apparent that the ⌬liaS mutant is more sensitive than LO28 to chloroxylenol, novobiocin, chloramphenicol, iodoacetate, doxycycline, pentachlorophenol, and sodium metaborate (Table 3). Chloroxylenol functions by disrupting the membrane potential of cells and is used in antibacterial soaps as well as being the active ingredient in the household antiseptic Dettol (44), novobiocin inhibits DNA gyrase, pentachlorophenol is used as a wood preservative and, previously, in disinfectant cleaners (46), iodoacetate is an inhibitor of glycolytic pathway enzyme GAPDH (glyceraldehyde-3-phosphate dehydrogenase) (43), and sodium metaborate is used in hard-surface cleaners to remove grease, rust, and scale from metal, glass, and detergents (24). It would thus seem that the status of the LiaSR system in L. monocytogenes impacts differently on the resistance of the pathogen to a variety of disinfectants and industrial hygiene agents.…”
Section: Resultsmentioning
confidence: 99%
“…It is not currently clear what phosphate concentration is critical for the onset of corneal calcification. Quite recently, preference has been given to borate buffers, which possess antimicrobial activity, showed good biocompatibility with the ocular surface both in vivo and in vitro and are considered safer [26,27]. Tris buffers are also included in some dosage forms and have been found to be effective and low toxic [28].…”
Section: Mtt Testmentioning
confidence: 99%